Soyasaponins Reduce Inflammation and Improve Serum Lipid Profiles and Glucose Homeostasis in High Fat Diet‐Induced Obese Mice. Issue 19 (29th August 2018) - Xie, Qunying; Gu, Xiangfu; Chen, Junbin; Liu, Minshun; Xiong, Fei; Wu, Xinglong; Zhang, Yajie; Chen, Fengping; Chen, Honger; Li, Meijuan; Sun, Suxia; Chu, Xinwei; et al.
Abstract : Scope: Obesity is linked to a chronic low‐grade inflammatory state that contributes to the development of obesity‐associated metabolic disorders. The anti‐inflammatory activities and mechanisms of soyasaponin monomers (A1, A2, and I) have been recently demonstrated in cell models. However, their potential in vivo abilities to reduce chronic inflammation and alleviate metabolic disorders in obese status remain unclear. Methods and results: High fat diet (HFD)‐fed obese male C57BL/6J mice are intervened by aspirin (0.1 mg kg –1 body weight) or 20 mg kg –1 of soyasaponins A1, A2, or I for 8 weeks. Soyasaponins A1, A2, and I significantly reduce pro‐inflammatory cytokines/mediators in serum, liver, and white adipose tissues (WATs), improve serum lipid profiles, decrease liver cholesterol, triglyceride and steatosis, and promote fecal excretion of cholesterol, triglycerides, and bile acids. Soyasaponins A1, A2, and I also decrease IKKα/β phosphorylation in liver and WATs and reduce NF‐κB p65 phosphorylation and CD68 mRNA and protein expression in WATs. Soyasaponins A1 and A2 but not I decrease NF‐κB p65 phosphorylation in liver and adipocytes hypertrophy in WATs. In addition, Soyasaponin A2 but not A1 nor I decreases fasting blood glucose and improved insulin resistance. Conclusion: Soyasaponins reduce inflammation and improve serum lipid profiles and glucose homeostasis in HFD‐induced obese mice. Abstract : Recently, the anti‐inflammatory activities of soyasaponin (SS) A1, A2, and I have been demonstrated by using in vitro cell models. Here, it is found that SSA1, SSA2, and SSI can reduce inflammation and improve serum lipid profiles in HFD‐fed obese mice. In addition, SSA2 can improve glucose homeostasis. These results provide new evidence supporting the in vivo anti‐inflammatory properties of SS and their ability to prevent obesity‐related metabolic dysfunction.